2000
DOI: 10.1067/mtc.2000.106520
|View full text |Cite
|
Sign up to set email alerts
|

Nontransplant Cardiac Surgery for End-Stage Cardiomyopathy

Abstract: Endoventricular circular patch plasty, partial left ventriculectomy, and solo valve reconstruction can be performed with an acceptably low risk as elective operations. The selection of operative procedures in idiopathic dilated cardiomyopathy and avoidance of emergency surgery improved operative mortality and morbidity. Among patients who survived at least 1 year, there were no late deaths up to 30 months' follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 26 publications
6
56
0
3
Order By: Relevance
“…1,2 In Japan, this procedure was first used in December, 1996, 6 but has had limited success in some institutes. 3,4,6 However, PLV is an acceptably safe and effective treatment for end-stage cardiomyopathy with proper choice of patients. 6 We previously reported that severe inflammatory cell infiltration might serve as a predictor of poor outcome in patients with DCM, 18,19 and the present study, which included a larger number of patients, demonstrated that the infiltrating inflammatory cell count was significantly greater in patients who died of left ventricular dysfunction after PLV than in patients who survived.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In Japan, this procedure was first used in December, 1996, 6 but has had limited success in some institutes. 3,4,6 However, PLV is an acceptably safe and effective treatment for end-stage cardiomyopathy with proper choice of patients. 6 We previously reported that severe inflammatory cell infiltration might serve as a predictor of poor outcome in patients with DCM, 18,19 and the present study, which included a larger number of patients, demonstrated that the infiltrating inflammatory cell count was significantly greater in patients who died of left ventricular dysfunction after PLV than in patients who survived.…”
Section: Discussionmentioning
confidence: 99%
“…9 The current indications and efficacy of partial left ventriculectomy for advanced heart failure in patients with dilated cardiomyopathy are controversial. 9,10 Because the systemic ventricle was markedly dilated in the present patient, and the lateral segment had a myocardial perfusion defect, we considered that systolic function could be improved by reducing the volume of the systemic ventricle, particularly by removing the fibrous segment as in aneurysmectomy. Recent reports indicate that mitral valve surgery can rescue patients with heart failure who have a dilated and poorly contracting left ventricle accompanied by moderate to severe mitral regurgitation, 10 but we considered that mitral replacement would not provide relief for this patient because he had already undergone that treatment 9 years before.…”
Section: Discussionmentioning
confidence: 99%
“…Matsui et al [18] reported the usefulness of integrated overlapping ventriculoplasty combined with papillary muscle plication for severely dilated heart failure. Suma et al [16] have showed that an intraoperative echographic evaluation is important for the purpose of proper site selection for ventricular reduction in end-stage cardiomyopathy. We performed an intraoperative echographic evaluation under the CPB in the present case, and confirmed that the contraction of the left ventricle was diffuse hypokinetic, especially severe hypokinetic in the anteroseptal wall, and that localization of changes in the LV wall thickness could not be observed.…”
Section: Discussionmentioning
confidence: 99%